Pasiones americanas: entramados afectivos en la literatura colonial. - Carneiro, Sarissa; Añón, Valeria (Colonial Latin American Review, 2022)
The article informs on affective frameworks present in the writing of colonial America. It mentions the terms passion and affection covered a wide semantic field, not necessarily coinciding with the current concept of emotions, their fields of application were both public and private, and included political, physical, spiritual, intellectual and emotional meanings artistic, this occurred in various cultural contexts during Early Modernity.